Development of environmentally friendly urban agricultural system through household waste utilization training in Jombang Indonesia - Anggi Indah Yuliana; Mucharommah Sartika Ami; Tholib Hariono (Universitas Ahmad Dahlan, Yogyakarta, 2021)
The development of residential areas in the Jombang Regency can increase global warming, so it needs urban greening in the area. The green environment can be done by developing an environmentally friendly urban agricultural system with 3R (Reduce, Reuse, Recycle) waste management. The skills of residents must support the utilization of domestic waste, so this is required adequate training activities. This training aimed to (1) increased the knowledge and skills of the residents in processed, domestic waste into compost and liquid organic fertilizer; (2) increased the knowledge and skills of residents in processed inorganic waste as a plant's pot; and (3) increased the spirit of citizens to live clean and healthy. This community service activity was carried out from 24 to July 26, 2020, with partner residents of the Bahrul Ulum Menara Asri, Jombang Regency. The program results showed that 76 percent of residents understood how to processed waste into compost, liquid organic fertilizer, and planting pots. Eighty-six percent of participants stated that the instructor's performance was very good, 88 percent of residents admitted that this training was useful in improving their skills in processed, domestic waste, and 86 percent of the participants planned to carry out waste processing practices in their homes.